Surface Characterization of Irradiated ZnO:Al Thin Film by Reactor Neutrons - Baydogan, N.; Cilingiryan, K.; Tugrul, A. B.; Cimenoglu, H.; Yesilkaya, S. S. (TRANS TECH PUBLICATIONS LTD, 2013)
Irradiation of ZnO:Al thin film by reactor neutrons with neutron/gamma ratio at 1.44x10(4) (n.cm(-2).s(-1).mR(-1)) leads to a decrease in resistivity in this material. The observed effects in electrical resistivity are attributed to irradiation-induced formation of defects in the ZnO:Al thin film structure.
Keywords: Coating; neutron irradiation; zinc oxide; Materials Science